2020
DOI: 10.11648/j.sr.20200804.12
|View full text |Cite
|
Sign up to set email alerts
|

M-Banking: The Transaction Revolution in Bangladesh

Abstract: Bangladesh is a developing country where mobile network operators had been started from 1993 through AMPS (Advanced Mobile Phone Service) and later on CDMA (Code-Division Multiple Access) technology was introduced and mobile banking facilities were started clearly under a guideline of the central bank of Bangladesh on 'Mobile Financial Services for Banks' in September 2011. Though m-banking is a newer service in the country meanwhile it has got very popularity within a short time due to inadequate traditional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…The previous studies also found that most of the users are dissatisfied with the high transaction charges of MFS (Hasan, 2020;Sarpong & Agbeko, 2020). In contrast, Alam et al (2013) found that most of the users believe mobile banking has a lower cost compared to traditional banking.…”
Section: Users' Experiences Of Perceived Costmentioning
confidence: 96%
“…The previous studies also found that most of the users are dissatisfied with the high transaction charges of MFS (Hasan, 2020;Sarpong & Agbeko, 2020). In contrast, Alam et al (2013) found that most of the users believe mobile banking has a lower cost compared to traditional banking.…”
Section: Users' Experiences Of Perceived Costmentioning
confidence: 96%
“…Bangladesh is a small country with six different mobile operators (Grameen phone, Robi, Teletalk, Airtel, Citycell, and Banglalink) [6] with a huge number of subscribers. According to the BTRC (Bangladesh Telecommunication Regulatory Commission) report in 2020, 10M [7] messages are delivered daily. There are various methods of defrauding individuals through misleading messages, such as by presenting unexpected offers.…”
Section: Introductionmentioning
confidence: 99%